Physico-Chemical and Antioxidative Properties of Whey Protein Beverages - Debasree Ghosh (Emerging Trends in Metabolites, 2024)
Whey, the liquid left after milk casein precipitation, was utilized, and its physicochemical properties were assessed. The aim of the research was to analyze the availability of nutrients in whey by preparing a modified whey protein beverage. Natural and artificial whey protein beverages were prepared. We studied the shelf life of these beverages over a period of 0 to 11 days and compared them based on their acidity, viscosity, pH, and organoleptic properties. It was studied by using students to test that, that natural whey beverage was curdled on day 7, whereas artificial whey beverage remained unaltered till day 11 of the study. The observation revealed that the natural whey beverage initially tasted better but curdled by the 7th day. In contrast, the artificial whey beverage, though initially unpalatable, improved in taste over time during storage. Among whey components, lactose is likely the least valuable and the most challenging to utilize. Different fruit concentrates, like apples, peaches, cherries, and berries, that are well-known sources of iron, magnesium, and antioxidants, are useful for the production of whey beverages with improved nutritional importance. Whey powder, whey concentrate, reduced mineral whey, whey protein concentrate, and lactose are used in human food; soil mixtures are mainly used in animal feed. Furthermore, the biological properties of whey protein have shown promise in the treatment of chronic diseases such as HIV, cancer, and cardiovascular diseases, and the nutrient-rich whey protein can be used in infant formula, adult formula, and sports nutrition.
Keywords: Cardiovascular disease; Whey protein; beverage; casein; functional food; lactose